Photoinduced copper-catalyzed enantioselective coupling reactions. (14th March 2023) - Song, Liangliang; Cai, Lingchao; Gong, Lei; Van der Eycken, Erik V.
Abstract : This review highlights the progress in photoinduced copper-catalyzed enantioselective coupling reactions. Abstract : Copper-catalyzed enantioselective coupling has been widely investigated, which allows rapid construction of various chiral molecules. Despite important advances via polar and radical mechanisms, exploring general and practical strategies for the regio-, enantio- and diastereoselective assembly of stereogenic centers is of significant value but remains highly problematic. The integration of photocatalysis with asymmetric copper catalysis could provide appealing access to the development of new reaction pathways and structurally diverse chiral compounds, and extend the boundaries of radical chemistry. This review summarizes recent advances in photoinduced copper-catalyzed enantioselective coupling reactions, and discusses the mechanistic aspects.